The effect of temperature and photoperiod on selected male reproductive characteristics in two seanonally breeding ( Cryptomys hottentotus hottentotus and Cryptomys hottentotus pretoriae ) and one aseasonally breeding mole-rat species ( Cryptomys damarensis ) - Bennett, Nigel Charles (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2005.